Determinant Factor for Stunting in Toddler - Widayati, Kurniasih; Putra, I kadek Agus Dwija; Dewi, Ni Luh Made Asri (Universitas Aisyah Pringsewu, 2021)
Stunting (failure to thrive) is a chronic nutritional problem in children under five which is characterized by a height that is shorter than its age. Stunting is a threat to the nation’s competitiveness. The side effects are disruption of brain development, intelligence, physical growth disorders, and metabolic disorders in the child’s body. The research objective was to determine the determinant factors causing stunting in Sukawati Gianyar District. The research design was a case-control with a sample size of 47 cases and 144 controls, all of which were selected within a certain time period, namely 1-16 August 2020 in Sukawati Subdistrict, Gianyar Regency. Cases were respondents whose height was less suitable for age and controls were toddlers with height according to age. Data were collected using a questionnaire that asks about maternal factors, child factors, environmental factors and health service factors. Univariate analysis is used to determine the characteristics of respondents, bivariate to determine OR and, multivariate logistic regression method to determine Adjusted OR. The bivariate analysis showed that the factors that increased the risk of stunting were maternal height with OR = 3,260 (95% CI: 1,567-6,783), Gravida OR = 2,719 (95% CI: 1,256-5,889), Birth weight with OR = 0.217 (95% CI: 0.165-0.286), Multivariate analysis showed that the determinant variable which significantly increased the risk of stunting was maternal height with OR = 3.5 (95% CI: 1.6-7.9), Gravida with OR = 3.394. (95% CI: 1.368-8.416) and breastfeeding initiation counseling with OR = 0.392 (95% CI: 0.158 0.974). Mother's height and Gravida are risk factors for stunting in Sukawati District, Gianyar Regency, Bali. Abstrak: Stunting (gagal tumbuh) merupakan masalah gizi kronis pada balita yang ditandai dengan tinggi badan yang lebih pendek dari usianya. Stunting merupakan ancaman bagi daya saing bangsa. Efek sampingnya adalah terganggunya perkembangan otak, kecerdasan, gangguan pertumbuhan fisik, dan gangguan metabolisme pada tubuh anak. Tujuan penelitian ini adalah untuk mengetahui faktor determinan penyebab stunting di Kecamatan Sukawati Gianyar. Rancangan penelitian adalah case control dengan ukuran sampel 47 kasus dan 144 kontrol yang semuanya dipilih dalam kurun waktu tertentu yaitu tanggal 1-16 Agustus 2020 di Kecamatan Sukawati Kabupaten Gianyar. Kasus adalah responden yang didapatkan tinggi badan kurang sesuai dengan umur dan kontrol adalah bayi dengan tinggi badan sesuai dengan umurnya. Data dikumpulkan menggunakan kuesioner yang menanyakan tentang faktor ibu, faktor anak, faktor lingkungan dan faktor pelayanan kesehatan. Analisis univariat digunakan untuk mengetahui karakteristik responden, bivariat untuk mengetahui OR dan, metode regresi logistik multivariat untuk menentukan Adjusted OR. Analisis bivariat menunjukkan bahwa faktor yang meningkatkan risiko stunting adalah tinggi badan ibu dengan OR = 3,260 (95% CI: 1,567-6,783), Gravida OR = 2,719 (95% CI: 1,256-5,889), Berat Badan Lahir dengan OR = 0,217 (95 % CI: 0,165-0,286), Analisis multivariat menunjukkan bahwa variabel determinant meningkatkan risiko stunting secara signifikan adalah tinggi badan ibu dengan OR = 3,5 (95% CI: 1,6-7,9), Gravida dengan OR= 3,394 (95%CI: 1,368-8,416) dan penyuluhan Inisiasi Menyusui Dini dengan OR=0,392 (95%CI: 0,158 0,974). Tinggi badan Ibu dan Gravida merupakan faktor risiko stunting di Kecamatan Sukawati Kabupaten Gianyar Bali.